Preparation and characterization of yttria stabilized zirconia (YSZ) films deposited by dip-coating on LSM-YSZ substrate with different proportions - Marrero,Jacqueline Costa (2019)
ABSTRACT In this work, sol-gel/dip-coating process for obtaining yttria stabilized zirconia (YSZ, ZrO2–8% Y2O3) films deposited onto LSM-YSZ (lanthanum strontium manganite (LSM, La0.7Sr0.3MnO3) mixed with YSZ) with different proportions (20/80, 50/50, 80/20) was investigated. The films were deposited on substrate varying the number of layers deposited. LSM powders were obtained by the combustion method using metal nitrates and urea and YSZ was commercial. LSM-YSZ composite powders were obtained by the solid state method, through ball-milling of a mixture of LSM-YSZ (mass ratio) powder for 4 h with 500 rpm using ZrO2 balls as milling media. For LSM-YSZ substrate a study of sintering temperature was performed, where the optimum sintering temperature for each LSM-YSZ studied proportion was obtained. According to our results, it was found that 1100 ºC is the optimum sintering temperature for 20/80, 950 ºC is the optimum sintering temperature for 50/50 and 900 ºC is the optimum sintering temperature for 80/20 because of the good phase formation. The films were characterized by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The films showed LSM, YSZ, SrZrO3 and La2O3 phases. Crack-free, homogeneous and well adhered films were obtained with a thickness between 3 and 38 µm. In this work, YSZ films with appropriate thickness were obtained for application as SOFC electrolyte.